(untitled) (Revista Contexto & Educação, 2026)
This paper aims to identify the relationships between communication and education in the Brazilian context, with an emphasis on the emergence of Educommunication. A historiographical approach is taken to examine recent Brazilian educational developments, focusing on state public policies and popular initiatives. In parallel, Paulo Freire’s praxis is analyzed as a precursor to the articulation between communication and education, offering theoretical and methodological foundations for the constitution of Educommunication. The results indicate that the integration of these fields enables the development of dialogical, horizontal, and emancipatory praxis, centered on the subjects and their critical formation. However, the consolidation of Educommunication is not free from tensions: its institutional appropriation—often disconnected from its critical foundations—can lead to conceptual dilution; furthermore, structural inequalities in access to technologies and media limit its transformative potential. Finally, it is emphasized that contemporary challenges—such as disinformation, algorithmic control, and surveillance logics in digital platforms—demand a critical update of educommunicative practices. It is concluded that Educommunication emerges as a theoretical and methodological field capable of mediating democratic and transformative educational practices, as long as it remains committed to its critical dimension and the expansion of participatory and civic conditions.